Exploration of Strategies to Overcome Dual-Triple Burden of Malnutrition in Adolescent Girls Based on Local Wisdom: A Qualitative Study - Sitti Patimah; Masriadi; Sharief, Suchi Avnalurini; Abbas, Hasriwiani Habo (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
The dual-triple burden of malnutrition among adolescent girls in Indonesia is a significant issue, particularly in West Sulawesi Province. Majene Regency has the second highest prevalence of malnutrition in the country, with alarming statistics showing that adolescent girls are affected by stunting (31.5%), anemia (17.9%), Chronic Energy Deficiency (KEK) (22.4%), and obesity (18.9%). This study aims to explore strategies for preventing and managing malnutrition based on local wisdom and cultural practices. The methodology includes qualitative-descriptive research through Focus Group Discussions (FGDs) and in-depth interviews with informants from four secondary schools in Majene District. Key informants include health service heads, nutrition officers, school principals, teachers, food vendors, parents, and female students. Their insights provide a comprehensive view of the challenges and potential solutions. The findings indicate several effective strategies: (1) changing mindsets about instant foods through education; (2) promoting healthy eating and local food consumption; (3) regular distribution of iron supplements in schools; (4) encouraging physical activity; (5) innovating healthy food services in school canteens; (6) revitalizing local government programs; and (7) securing funding through School Operational Assistance and Village funds to support these initiatives. In conclusion, there are several local wisdom-based strategies that can be implemented to address malnutrition among adolescent girls. It is suggested that the results of this research can be a valuable reference for local governments, educators, and various stakeholders who are committed to improving the nutritional-health status of adolescent girls.